2019
DOI: 10.1183/23120541.00234-2018
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous sulfur hexafluoride and nitrogen multiple-breath washout (MBW) to examine inherent differences in MBW outcomes

Abstract: Multiple-breath washout (MBW) can be performed with different gases (sulfur hexafluoride (SF6­) and nitrogen (N2)) and different devices, all of which give discrepant results. This study aimed to confirm previously reported differences and explore factors influencing discrepant results; equipment factors or the physical properties of gases used.MethodsHealthy controls (HCs) and participants with cystic fibrosis (CF) completed MBW trials on two commercially available devices (Exhalyzer D (N2) and Innocor (SF6))… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
(47 reference statements)
1
15
1
Order By: Relevance
“…This error appears to be more pronounced in disease but has also been seen in healthy subjects [13]. The reasons for this are unclear, and may relate to the contribution of body nitrogen to the washout or to issues with specific analyser technologies [34,35]. In this study however, we saw no consistent deviation in FRC values from those predicted, with a mean difference of only 0.06L from predicted FRC.…”
Section: Discussioncontrasting
confidence: 53%
“…This error appears to be more pronounced in disease but has also been seen in healthy subjects [13]. The reasons for this are unclear, and may relate to the contribution of body nitrogen to the washout or to issues with specific analyser technologies [34,35]. In this study however, we saw no consistent deviation in FRC values from those predicted, with a mean difference of only 0.06L from predicted FRC.…”
Section: Discussioncontrasting
confidence: 53%
“…While SF 6 may not reach very poorly ventilated regions during wash-in, endogenous N 2 may prolong wash-out from these regions resulting in higher LCI values. Hence, attention has to be paid to test gas choice when interpreting MBW results 59 . Despite the above-mentioned potential advantages of SF 6 -MBW, it should be noted that tracer gas still is associated with considerable costs.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of the nitrogen multiple breath washout (MBW) method to measure lung clearance index (LCI) using the Exhalyzer device (Eco Medics AG, Dürnten, Switzerland), BAYFIELD et al [1] reported an N 2 offset signal of ∼1.4%, slightly higher than reported in several previous studies. There was no similar offset using sulfur hexafluoride as the tracer gas measured with the Innocor device (Innovision ApS, Glamsbjerg, Denmark), a finding that is in line with previous reports.…”
Section: To the Editormentioning
confidence: 85%